Linking Innate and Adaptive Immunity: Human Vγ9Vδ2 T Cells Enhance CD40 Expression and HMGB-1 Secretion - Shirin Kalyan; Anthony W. Chow (Mediators of Inflammation)
γδ T cells play an important role in regulating the immune response to stress stimuli; however, the mean by which these innate lymphocytes fulfill this function remains poorly defined. The main subset of human peripheral blood γδ T cells responds to nonpeptidic antigens, such as isopentylpyrophosphate (IPP), a metabolite in the mevalonate pathway for both eukaryote and prokaryote cells. IPP-primed γδ T cells significantly augment the inflammatory response mediated by monocytes and αβ T cells to TSST-1, the staphylococcal superantigen that is the major causative agent of toxic shock syndrome. Here we show that the small pool of activated peripheral γδ T cells induces an early upregulation of CD40 on monocytes and the local release of High Mobility Group Box-1 (HMGB-1), the molecule designated as the late mediator of systemic inflammation. This finding provides a new basis for how γδ T cells may serve as influential modulators of both endogenous and exogenous stress stimuli.